The Right of Access to Environmental Information in Ukraine and the EU - Ladychenko, Viktor; Golovko, Liudmyla (European Journal of Sustainable Development, 2018)
The purpose of our scholarly work is to explore legal regulation of access to environmental information and public participation in environmental decision-making in Ukraine and the EU. The article considers how the Aarhus Convention has been implemented in EU member states and Ukraine, concentrating on the public access to information as a valid instrument for environmental protection. Taking part in the Erasmus + Jean Monnet Module "EU Environmental Policy and Law" we have analyzed the possibility of obtaining operative environmental information on the state of the environment in cities and villages of Ukraine. We also have studied European standards in the sphere of disclosure of environmental information and public participation, found some gaps in Ukrainian legislation and filled them in. We offer an interdisciplinary approach: integration of information law, environmental law, international law, human rights and national security. This will allow us to form a conceptual understanding of the legal regulation of information on the environment as an object of realization of information human rights and a component of national security in the context of environmental threats. Keywords: Environmental information, information human rights, sustainable development, EU environmental policy